TaniSidemen: Aplikasi Pengadaan dan Penjualan Bibit biji Tanaman berbasis Mobile - Maulana, Muhammad Hizbi; Asriningtias, Yuli (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Procuring and selling seeds is an important part of sustainable agriculture. To facilitate this process, mobile applications are a promising solution. This research aims to develop a mobile application specifically designed for the procurement and sale of plant seedlings. The method used for the development of this software is Software Development Life Cycle (SDLC) with waterfall approach. The planning stage is carried out for system planning, the analysis stage is carried out to analyze the running system and collect data by conducting observations and interviews, the design stage is carried out to design use case diagrams, activity diagrams and user interfaces, the implementation stage uses Kotlin when the implementation process and the testing stage uses black box testing. The results of black box testing are the main functionality of applications such as procurement and sales menus that work properly. The result of this research is an application called TaniSidemen, which is a mobile-based plant seed procurement and sales application. The TaniSidemen application facilitates the procurement and sale of plant seeds, increases time and cost efficiency, and supports the digitization of the agricultural sector for industrial sustainability.